Initial testing (stage 1) of the PARP inhibitor BMN 673 by the pediatric preclinical testing program: PALB2 mutation predicts exceptional in vivo response to BMN 673. Issue 1 (27th September 2014) - Smith, Malcolm A.; Hampton, Oliver A.; Reynolds, C. Patrick; Kang, Min H.; Maris, John M.; Gorlick, Richard; Kolb, E. Anders; Lock, Richard; Carol, Hernan; Keir, Stephen T.; Wu, Jianrong; Kurmasheva, Raushan T.; et al.
<x xml:space="preserve">Abstract</x> Background BMN 673 is a potent inhibitor of poly‐ADP ribose polymerase (PARP) that is in clinical testing with a primary focus on BRCA‐mutated cancers. BMN 673 is active both through inhibiting PARP catalytic activity and by tightly trapping PARP to DNA at sites of single strand breaks. Procedure BMN 673 was tested in vitro at concentrations ranging from 0.1 nM to 1 μM and in vivo at a daily dose of 0.33 mg/kg administered orally twice daily (Mon‐Fri) and once daily on weekends (solid tumors) for 28 days. Results The median relative IC50 (rIC50) concentration against the PPTP cell lines was 25.8 nM. The median rIC50 for the Ewing cell lines was lower than for the remaining cell lines (6.4 vs. 31.1 nM, respectively). In vivo BMN 673 induced statistically significant differences in EFS distribution in 17/43 (39.5%) xenograft models. Three objective regressions were observed: a complete response (CR) in a medulloblastoma line (BT‐45), a maintained CR in a Wilms tumor line (KT‐10), and a maintained CR in an ependymoma line (BT‐41). BMN 673 maintained its high level of activity against KT‐10 with a threefold reduction in dose. KT‐10 possesses a truncating mutation in PALB2 analogous to PALB2 mutations associated with hereditary breast and ovarian cancer that abrogate homologous recombination (HR) repair. Conclusions The PPTP results suggest that single agent BMN 673 may have limited clinical activity against pediatric cancers. Single agent activity is more likely for patients whose tumors have defects in HR repair. Pediatr Blood Cancer 2015;62:91–98. © 2014 Wiley Periodicals, Inc.